Efektifitas Kebijakan Pengurangan Sanksi Administrasi dalam Meningkatkan Kepatuhan Wajib Pajak di Kantor Wilayah DJP Jakarta Utara Tahun 2023 - Muhammad Reza Anindiarto; M. Agus Cholik (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
This study aims to assess the effectiveness of the implementation of the administrative sanction reduction policy applicable at the North Jakarta Regional Tax Office in 2023 in improving taxpayer compliance. The study uses a qualitative descriptive method where research data is obtained through interviews, observations, documentation, and literature studies. The results of this study indicate that the Effectiveness of the Administrative Sanction Reduction Policy in Increasing Taxpayer Compliance at the North Jakarta Regional Tax Office in 2023 is quite effective, although one of the effectiveness measurement indicators still needs improvement. Based on the achievement of the goal indicator, the implementation of the administrative sanction reduction policy has met the provisions of the deadline for completing the application for administrative sanction reduction and the administrative sanction reduction policy in 2023 can also increase taxpayer compliance in submitting the Annual Income Tax Return. The results of the study on the integration indicator related to socialization show that the socialization of the administrative sanction reduction policy in 2023 has been carried out to internal parties but has not been carried out evenly and comprehensively to all taxpayers at the North Jakarta Regional Tax Office. The results of the study on the adaptation indicator indicated by the ability to synergize and adapt to the diversity of cases in the application show that the implementers of the administrative sanction reduction policy have the ability to synergize with parties related to the process of completing the application for administrative sanction reduction and can adapt to the diversity of cases and problems in completing the administrative sanction reduction process so that these factors can support the effectiveness of the implementation of the administrative sanction reduction policy in increasing taxpayer compliance at the North Jakarta Regional Tax Office.Keywords: Effectiveness; Reduction of Administrative Sanction; Taxpayer Compliance.